Kajian Stakeholders dalam Pengembangan Kampung Wisata Warna-Warni Berkelanjutan dan Aman Bencana di Bantaran Sungai Brantas - Kevie Desderius; Arief Hargono; Aditya Prana Iswara (Jurnal Penataan Ruang, 2025)
The Colorful Tourism Village in Malang City is one of the tourism destinations located on the banks of the Brantas River. As one of the tourist attractions that many tourists visit, it is necessary to pay attention to stakeholders who can support the development of the tourism area. Understanding the role of each stakeholder is important because the area is located on the banks of rivers that are prone to various disaster threats. The purpose of this study is to identify the stakeholders involved, the role of each stakeholder and the relationship between stakeholders as well as supporting and inhibiting factors. The research method used uses a qualitative descriptive approach with data collection based on literature studies, documentation and observations. Based on the results of the study, it is known that the development of a disaster-safe Colorful Tourism Village on the banks of the Brantas River, Malang City involves various stakeholders with the concept of pentahelix, consisting of academics, business, communities, government and mass media. Each stakeholder involved is classified into primary, key and secondary stakeholders. The role of stakeholders is reflected in the role of policy creator, coordinator, facilitator, implementer and accelerator. The relationship between stakeholders is seen from the form and activity. There are several supporting and inhibiting factors in the development of the area.